2009
DOI: 10.2139/ssrn.1517112
|View full text |Cite
|
Sign up to set email alerts
|

Time Varying Risk Aversion: An Application to Energy Hedging

Abstract: Risk aversion is a key element of utility maximizing hedge strategies; however, it has typically been assigned an arbitrary value in the literature. This paper instead applies a GARCH-in-Mean (GARCH-M) model to estimate a time-varying measure of risk aversion that is based on the observed risk preferences of energy hedging market participants. The resulting estimates are applied to derive explicit risk aversion based optimal hedge strategies for both short and long hedgers. Out-of-sample results are also prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, in traditional GARCH-M model, a hypothesis is actually implied: in a certain period, the risk compensation the investor demands for each unit of risk is fixed. However, [39][40][41] find that people's risk attitude is changing with time. The greater the extent of risk aversion is, the more the compensation return the investor demands for each unit of risk.…”
Section: The Thoughts Of Empirical Analysismentioning
confidence: 99%
“…However, in traditional GARCH-M model, a hypothesis is actually implied: in a certain period, the risk compensation the investor demands for each unit of risk is fixed. However, [39][40][41] find that people's risk attitude is changing with time. The greater the extent of risk aversion is, the more the compensation return the investor demands for each unit of risk.…”
Section: The Thoughts Of Empirical Analysismentioning
confidence: 99%
“…Risk preference tends to focus on behaviors involving higher variance in audits, regardless whether they are beneficial or detrimental (Cotter & Hanly, 2010). Auditors with high risk preferences have a high level of confidence and they are bolder in taking high risks.…”
Section: H1mentioning
confidence: 99%
“…Previous studies found that investors' risk aversion varies at different time periods ( [33,34], etc.). The higher risk aversion means higher return compensation investors demand for unit risk they take, which implies that the risk premium coefficient should vary with time and other factors.…”
Section: Time Variation Of Risk Premium Coefficientmentioning
confidence: 99%